Management of transitional cell carcinoma by targeting the epidermal growth factor receptor. Issue 3 (May 2006) - Brook, Nicholas R; Colquhoun, Alex J; Mellon, J Kilian
The epidermal growth factor receptor (EGFR) family and its ligands play a central role in the development and progression of urothelial transitional cell carcinoma. Alterations in receptor physiology are associated with propagation of malignancy, and overexpression is an adverse prognostic feature associated with decreased survival. Knowledge of abnormalities in EGFR physiology has been harnessed to explore potential avenues for treatment. Strategies for inhibition or abrogation of the EGFR signal in the setting of transitional cell carcinoma include the application of anti-EGFR antibodies and EGFR tyrosine kinase inhibitors as sole and salvage agents, and as adjuvant treatment with chemotherapy and radiation. These novel drugs may permit greater treatment efficacy, reduced toxicity and improved organ preservation in this common disease.